2018
DOI: 10.1161/circulationaha.117.028268
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin and Clinical Outcomes in Patients With Type 2 Diabetes Mellitus, Established Cardiovascular Disease, and Chronic Kidney Disease

Abstract: URL: https://www.clinicaltrials.gov. Unique identifier: NCT01131676.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
275
0
26

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(309 citation statements)
references
References 33 publications
8
275
0
26
Order By: Relevance
“…The EMPA-REG OUTCOME study also demonstrated impressive beneficial renal outcomes (7). Compared with placebo, empagliflozin treatment was associated with a 46% risk reduction in the composite of doubling of serum creatinine, initiation of renal replacement therapy (dialysis or renal transplant), or death caused by renal disease (P = 0.0002) ( Table 2).…”
mentioning
confidence: 94%
“…The EMPA-REG OUTCOME study also demonstrated impressive beneficial renal outcomes (7). Compared with placebo, empagliflozin treatment was associated with a 46% risk reduction in the composite of doubling of serum creatinine, initiation of renal replacement therapy (dialysis or renal transplant), or death caused by renal disease (P = 0.0002) ( Table 2).…”
mentioning
confidence: 94%
“…The EMPAREG trial looked at the effects of empagliflozin [17]. When we look at cardiovascular death in people with or without prevalent kidney disease, and the endpoint for hospitalization for heart failure, the effects are consistent in both subgroups, regardless of the prevalence of kidney disease or not.…”
Section: Diabetic Nephropathy: Hiddo Lambers Heerspink (The Netherlands)mentioning
confidence: 99%
“…In EMPA-REG OUTCOME trial (empagliflozin cardiovascular event outcome event trial in type 2 diabetes mellitus (T2DM) patients) [22,23], the effect of empagliflozin was studied on cardiac outcomes in patients with T2DM. However, worsening renal end points (defined as progression to macroalbuminuria [UACR to 300mg/gm], doubling of serum creatinine, dialysis, or mortality from renal causes) was one of the secondary outcomes in this study.…”
Section: Therapiesmentioning
confidence: 99%